Amalan Pembelajaran Hifz al-Quran Pelajar Tahfiz Model Ulul Albab (TMUA) Sekolah Menengah Kebangsaan Agama di Malaysia: The Learning Practice of Hifz al-Qur’an among Tahfiz Model Ulul Albab (TMUA) Students at National Religious Secondary School in Malaysia - Kaimin, Siti Khadizah; Yussuf, Ahmad; Mohd Yusoff, Mohd Yakub & Zulkifli (Jurnal Usuluddin, 2025)
The objective of my research is to study and explore student practice Hifz al-Quran to learn Tahfiz Model Ulul Albab (TMUA) at National Religious Secondary School in Malaysia. The learning practice of Hifz al-Quran of TMUA students was studied from four aspects such as beginning of learning, during learning, closing learning and use learning materials. 350 students form 4 high school from the Nasional Religion under the Tahfiz Model Ulul Albab (TMUA) program were involved. The survey design benefit quantitative approach that use a descriptive method. Referring to the previous studies and content verified by the experts, the questionnaire instrument was created by author. The quantitative data from the questionnaire had been analyzed by descriptively using statistical package for social sciences (SPSS) version 28 to receive repetition, percentage, minutes and standard deviation. As a result of the research that the learning practices of TMUA students from the beginning aspects of learning and during learning is a high level, whereas the closing of learning carry out 89.7 percent (314), min 4.41 is a very high level. However, the aspects of learning method is in min 2.52 which is at lower level. The reason use of laptop, LCD Smart phone, al-Quran CD and audio al-Quran is smaller amount in practice learning Hifz al-Quran. In the learning al-Quran should be developed with several learning methods together with the technological advance in this stage, so that the increase in domination of Hifz al-Quran can maximized to the student and more interested in learning al-Quran at school. In the event of this study, it is expected to contribute to the success of Tahfiz learning in improve students Hifz al-Quran achievement.